Coagulation factors as potential predictors of COVID-19 patient outcomes (Faculty of Medicine Universitas Indonesia, 2023)
BACKGROUND Causes of death and length of hospitalization in patients with COVID-19 have been associated with coagulopathy. The coagulopathy mechanism involves the process of coagulation and endothelial damage triggered by an inflammatory response of the SARS-CoV-2 infection due to excessive release of proinflammatory cytokines. This study aimed to determine the association of coagulation factors as potential predictors of COVID-19 patient outcomes. METHODS This retrospective study was performed on 595 patients at Wahidin Sudirohusodo Hospital, Makassar, from June 2020 to June 2021. Participants were recruited using total sampling and assessed for COVID-19 severity using the World Health Organization classification and coagulation factors (D-dimer, fibrinogen, thrombocyte, and prothrombin time [PT]). Patient outcome assessments were survival and length of hospitalization. RESULTS We found a significant sex-based disparity, with a higher COVID-19 incidence in males. Severe cases were more common among those aged >50 years, with prolonged hospitalization (>10 days) linked to higher severity (odds ratio [OR] = 2.22, 95% confidence interval [CI] = 1.31–3.77, p<0.001). Elevated fibrinogen and D-dimer levels, as well as prolonged PT, predicted severe cases. However, D-dimer had the highest influence compared to other coagulation factors (OR = 14.50, 95% CI = 5.85–35.95, p<0.001), while prolonged PT influenced mortality rates (OR = 4.02, 95% CI = 1.35–12.00, p = 0.01). CONCLUSIONS Coagulation factors, such as elevated D-dimer and fibrinogen levels and prolonged PT, predicted the severity of COVID-19 patients leading to death.